Isolated Flexor Tenosynovitis as the Sole Manifestation of Rheumatoid Arthritis: A Case Report - Pradeep Kumar Pathak; Priti Ranjan Sinha; Pranjal Agrawal; Nikhil Gupta; Siddharth Jain (Journal of Orthopaedic Case Reports)
Introduction: Chronic volar wrist swelling is a diagnostic challenge, particularly in tuberculosis-endemic regions, where both infectious and inflammatory causes must be considered. Rheumatoid tenosynovitis, an extra-articular manifestation of rheumatoid arthritis (RA), can mimic infectious tenosynovitis, especially in seronegative patients. Case Report: We report a case of a 44-year-old male presenting with progressive pain and swelling over the volar aspect of the right wrist for 2 months. Clinical findings of a local rise in temperature, tenderness, and limitation of range of motion suggested flexor tendon tenosynovitis, with differential diagnoses including abscess, tuberculous tenosynovitis, Giant cell tumours, or inflammatory arthritis. Ultrasound and magnetic resonance imaging revealed tendon sheath thickening and features of median nerve compression. The patient had elevated inflammatory markers, but rheumatoid factor and anti-cyclic citrullinated peptide were negative. Excision biopsy and synovectomy with median nerve decompression were performed. Surgical exploration revealed hypertrophied synovium around the flexor tendons. Histopathology confirmed a rheumatoid nodule, establishing the diagnosis of rheumatoid tenosynovitis despite negative serology. The patient’s recovery was uneventful postoperatively. Conclusion: This case highlights the importance of considering rheumatoid tenosynovitis in the differential diagnosis of chronic wrist swelling, even in seronegative individuals. In ambiguous cases, surgical intervention not only alleviates symptoms but also allows for definitive diagnosis through histopathology. A multidisciplinary and vigilant approach is crucial to prevent misdiagnosis and preserve hand function in such presentations.